Large linewidth reduction in semiconductor lasers based on atom-like gain material - Septon, Tali; Becker, Annette; Gosh, Sutapa; Shtendel, Gal; Sichkovskyi, Vitalii; Schnabel, Florian; Sengill, Anna; Elica, Marko Bj; Witzigmann, Bernd; Reithmaier, Johann Peter; Eisenstein, Gadi (Optica, 2019)
With a new generation of quantum dot (QD) optical gain material comprising atom-like features, the fundamental spectral characteristics of laser emission have been improved significantly. We describe the spectral and power characteristics of continuous wave (CW) single-mode InAs/AlGaInAs/InP QD distributed feedback lasers operating at 1.5 μm. Linewidths as narrow as 60 kHz (30 kHz ± 10 kHz intrinsic linewidth) at 20°C, which broadens to only 280 kHz (80 kHz ± 10 kHz intrinsic linewidth) at 80°C, have been achieved. The laser exhibits high output powers of 58 mW at 20°C and 26 mW at 80°C with side mode suppression ratios exceeding 50 dB. These record values stem from high uniformity of the QDs and a large dot density. The linewidth was measured by two techniques that confirm each other: delayed self-heterodyne interferometry and optical frequency comb interferometry. A model fits the experimental results well and enables extraction of the bias and temperature dependent α parameter. At 20°C, α is less than 0.5 at threshold and increases to only 0.9 at 150 mA above threshold. The corresponding values at 80°C are 2 and 2.5. These results imply a great potential of QD lasers for the most demanding applications in terms of spectral purity, such as coherent optical communication systems and optical metrology.
CRIS-Team Scopus Importer:2021-06-11